Experiences and needs of parents of babies treated for congenital duodenal obstruction - A qualitative study - Henrik Røkkum; Anders Telle Hoel; Kristin Bjørnland (Elsevier, 2023)
Background: Knowledge about experiences and needs of parents of babies operated for congenital gastrointestinal anomalies in the neonatal period is very limited. Therefore, we performed this qualitative study to explore the experiences and needs in this group of parents. Methods: Parents of babies operated for congenital duodenal obstruction participated in a focus group discussion. The focus group discussion was analyzed with hermeneutical interpretation, and themes representing important areas to the parents were identified. Results: Six parents of five babies participated. Four themes evolved from the focus group discussion. "Grief over loss of initial parent-child bonding" describes the feeling of being separated from the baby during initial treatment. "Let me take care of my baby" refers to the importance for the parents to be involved in caring for their baby. "Concerns about breastfeeding" reflects the mothers' worries about and need for encouragement and guidance regarding pumping and breastfeeding. "Trusting health care providers" implies that the parents were confident that their baby was well taken care of, despite an emotionally stressful situation. Conclusions: This qualitative study provides new and important knowledge regarding the experiences and needs of parents of babies operated for congenital duodenal obstruction. The results may be generalizable to other gastrointestinal anomalies needing surgery. This new knowledge may help health care providers to better meet the needs in parents of a baby having undergone repair of gastrointestinal anomaly. Level of evidence: IV